Influential aspects in the perception of the Flipped Classroom of a marketing course - Beirute Miranda, Francisco Javier (2020)
To increase the innovation during the teaching process, Flipped Classroom strategy was used, for the first time, in two Marketing courses at the Hispanoamerican University of Costa Rica. The main goal of the study was to analyze the students perceptions about this strategy in the third Marketing Seminar. The research considered four main aspects: the teachers role, the quality of the new knowledge, the freedom of expression during class, and the level of students; enjoyment. The perceptions also taken into consideration for the analysis. This study was quantitative and non-experimental. A questionnaire was used as the main instrument for gathering data. The overall perception of the strategy was positive: it was considered that it increased the learning process, aided concept memorization and understanding, and increased theenjoyment during class. linked to the evaluation process were.